Study of the effect of Lactobacillus crispatus FSCDJY67L3 on Helicobacter Pylori eradication: a double-blind randomized controlled clinical trial - Hong, Qing; Wang, Jidong; Zhang, Huayue; Liu, Xiaoming; Liu, Zhenmin (Frontiers in Immunology, 2023)
Helicobacter pylori (H. pylori) is a gram-negative bacterium exhibiting high pathogenicity. Traditional antibiotic treatments were considered ineffective as the H. pylori resistance increased. Recently, a quadruple therapy strategy of probiotics and antibiotics to eliminate H. pylori was proposed. Probiotics play a therapeutic role as supplements in this process. A probiotic strain (Lactobacillus crispatus FSCDJY67L3) that co-aggregates strongly with H. pylori was screened in this research. L. crispatus FSCDJY67L3 was demonstrated to significantly reduce H. pylori load ( 14 C breath test) in clinical trials with H. pylori positive patients. Gastrointestinal Symptom Rating Scale (GSRS) score was decreased, indicating improvement in the gastrointestinal discomfort of patients. Furthermore, L. crispatus FSCDJY67L3 showed no change in the structure of the intestinal flora of patients. Routine blood indices and blood biochemical indices related to liver and kidney function were also not affected in the patients. Therefore, L. crispatus FSCDJY67L3 may be used clinically as a supplement for the treatment of H. pylori.